No association between ACE gene variation and endurance athlete status in Ethiopians - Ash, G. I.; Scott, R. A.; Deason, M.; Dawson, T. A.; Wolde, B.; Bekele, Z.; Teka, S.; Pitsiladis, Y. P. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The most widely studied candidate gene for endurance performance is the angiotensin-converting enzyme (ACE) gene. The best endurance runners in the world hail from Kenya and Ethiopia, so the lack of association between the ACE gene and elite endurance athlete status we previously reported in Kenyans requires replication in Ethiopians.